Inquiry research trends through bibliometric analysis (2020-2023) - Lismaya, Lilis; Wiyanto , Wiyanto; Ridlo, Saiful (Biosfer: Jurnal Pendidikan Biologi, 2024)
This article aims to analyze the trend of Inquiry research through bibliometrics in the Google schoolar database from 2020 to 2023. The article consists of a total of 993 articles, then sorted into 788 suitable articles and analyzed. The method used in this research is article analysis using bibliometrics with the following stages: keyword search, initial search results, refining search results, compiling initial data, and data analysis. The results show that publications in scientific articles regarding Inquiry vary every year. Then, the description in Education research trends produces seven clusters, namely science process skills, science teacher, argument driven inquiry, framework, experience, critical thinking skills, and senior high school. The findings of this study are expected to help other researchers who are interested in studying and researching related to Inquiry research trends and recommend directions for further research